2022
DOI: 10.1021/jasms.2c00261
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Matrix pKa on Molecular Ion Formation in Matrix-Enhanced Secondary-Ion Mass Spectrometry

Abstract: Time-of-flight secondary ion mass spectrometry (ToF-SIMS) is one of the most important techniques for chemical imaging of nanomaterials and biological samples with high lateral resolution. However, low ionization efficiency limits the detection of many molecules at low concentrations or in very small volumes. One promising approach to increasing the sensitivity of the technique is by the addition of a matrix that promotes ionization and desorption of important analyte molecules. This approach is known as matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…This can be related to the increase in the ion signal of the fragment but also to the fragmentation induced during the transfer with the Ar cluster beam. However, the [PC(34:1) + H] + /PC HG secondary ion yield ratio is greatly increased upon transfer on CHCA (SI, Figure S6B), showing that, in agreement with other studies, 16,48,49 the matrix enhances the formation of [M + H] + ions through at least two mechanisms, by reducing the fragmentation and donating protons.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This can be related to the increase in the ion signal of the fragment but also to the fragmentation induced during the transfer with the Ar cluster beam. However, the [PC(34:1) + H] + /PC HG secondary ion yield ratio is greatly increased upon transfer on CHCA (SI, Figure S6B), showing that, in agreement with other studies, 16,48,49 the matrix enhances the formation of [M + H] + ions through at least two mechanisms, by reducing the fragmentation and donating protons.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…This result was anticipated since CHCA is a cinnamic acid of p K a of 1.17 and proton donation plays a major role in the formation of molecular ions for those kinds of matrices. Previous studies have demonstrated a correlation between decreasing p K a and increasing protonated positive ion, especially for halogen-substituted cinnamic acid derivatives …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…This approach mimics what has been done in matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS). A variety of matrix compounds have been demonstrated to improve ion yield in SIMS, including both compounds used in MALDI-MS as well as compounds that are unsuitable for MALDI-MS. …”
Section: Introductionmentioning
confidence: 99%